Hubungan Perilaku Penggunaan Alat Pelindung Diri (Apd) Dan Pelaksanaan Pencegahan Covid-19 Dengan Kecemasan Perawat Di Rumah Sakit X, Kalimantan Barat - Hany Wihardja; Roibertus Totong; Rosa Nora Lina (Unit Penelitian dan Pengabdian Kepada Masyarakat, STIKES Dirgahayu Samarinda, 2023)
Anxiety is a negative feeling due to situation that cause discomfort, uncertainty, helplessness, and isolation. The Covid-19 pandemic is one of triggers for anxiety in nurses because the virus is easily transmitted quickly. This study aims to identify a relationship between the behavior of using Personal Protective Equipment (PPE) and the implementation of the Covid-19 prevention protocol with nurses’ anxiety. This research is quantitative research using a descriptive correlation design with a Cross Sectional approach. Respondents in this study involved nurse practitioner who treated non-Covid-19 patients at RS X, West Borneo, with a purposive sampling technique. Nurses’ anxiety in treating non-Covid-19 patients is included in the category of mild anxiety (1 – 17) using Hamilton Anxiety Rating Scale (HARS) questionnaire. Analysis of the data using the Spearman Rho test, which obtained the results that there was no relationship between the behavior of using PPE and the implementation of the Covid-19 prevention protocol with the anxiety of nurses. The recommendation from the result of this study is stakeholders must prioritize the mental health of nurses by making regulation and socializing Covid-19 prevention protocols in the hospital environment for nurses.